Darf ich mit einer Erkältung trainieren? - Gmünder, F. K.
On the question if an athlete (swimmer) should train with an infection. Conclusions I is recommended: No workouts when you have a temperature If you have a cold with a sore throat: No workouts If you have a cold, no temp, no sore throat, i.e. only a running nose, you may swim, but only at a very low aerobic - pace. No anaerobic and speed work. Check your heart rate to be sure.